Conformational analysis of cinhonine and cinhonidine by tensor decomposition of molecular dynamics trajectories - Sović, Karlo; Ostojić, Tea; Cepić, Sara; Ramić, Alma; Odžak, Renata; Skočibušić, Mirjana; Hrenar, Tomica; Primožič, Ines (2019)
Full conformational space of cinchonine and cinchonidine has been investigated by means of statistical analysis of quantum chemical molecular dynamics simulations. Recently developed procedure comprising principal component analysis of molecular dynamics trajectories was applied on cinchonine and cinchonidine as well as on their protonated and methylated quaternary derivatives. The method for full conformational analysis includes Cartesian coordinates sampling through quantum chemical molecular dynamics simulations, reduction of dimensionality by principal component analysis, determination of probability distributions in a reduced space of Cartesian coordinates and search for all the strict extrema points in probability distribution functions. In order to gain crucial insight in the understanding of chirality induction of these alkaloids, comparison of the determined conformational spaces of pseudo-enantiomers has been made. It was shown that protonation of the quinuclidine nitrogen atom stabilizes the conformers with the intramolecular 1N–H∙∙∙9O hydrogen bond whereas methylation on the same position results in the reduction of the domain of internal coordinates responsible for the conformational space.
Bibliografija: 33 jed.
Abstract.
Keywords: Konformacijska analiza -- Alkaloidi -- Stereokemija -- Kvantno-kemijski računi -- Analiza glavnih komponenata -- Molekularna dinamika -- Biološka aktivnost -- Protuupalno djelovanje -- Antimalarični učinak -- Antiaritmijsko djelovanje